Consumer Trust in Mediating the Impact of Service Quality on Purchase Decisions - Misi, Triana; Yendra, Yendra; Marihi, La Ode (Advances: Jurnal Ekonomi & Bisnis, 2024)
Purpose: This study explores the relationship between service quality, consumer trust, and purchase decisions in the context of the Jequilla florist business. Research Design and Methodology: This study used quantitative design with a cross-sectional approach. Data was collected through questionnaires from 120 randomly selected consumers of Jequilla florist. The variables measured include service quality, consumer trust, and purchasing decisions. Data was analyzed using Structural Equation Modeling (SEM) with AMOS 26 software. Findings and Discussion: The results show that service quality does not directly influence purchasing decisions. However, service quality has a significant effect on consumer trust, and this consumer trust significantly affects buying decisions. This suggests that building consumer trust through service quality is a key factor influencing purchasing decisions. Implications: This research contributes to business practice and policy to improve service quality and build consumer trust. Florist business management is advised to focus on transparency, consistency, and responsiveness in service. Further research is recommended using a longitudinal design and considering other variables such as price and promotion to provide more comprehensive insights.